INOCULATION AND PHOSPHORUS APPLICATION EFFECTS ON SOYBEAN [Glycine max (L.) Merrill] PRODUCTIVITY GROWN IN FARMERS’ FIELDS OF BENIN - C. C. Zoundji; P. Houngnandan; M. H. Amidou; F. A. Kouelo; F. Toukourou (Journal of Animal and Plant Sciences, 2015)
Nitrogen deficiency is a major factor limiting crop production in most African agricultural soils. As legume, soybean can obtain a significant amount of its N requirement through symbiotic N2 fixation when inoculated with effective and compatible Bradyrhizobium strains. An on farmer’s fields’ study was carried out in Northern and Centre Benin to determine the effectiveness of Bradyrhizobium japonicum strains introduced in Benin cropping systems. Five inoculations treatments (control, FA3, STM3043, STM3045 and USDA110), two phosphorus levels (0 and 50 kg of P2O5 ha-1) arranged in split plot design were established in twelve farmers’ fields. Each farmer represented one replication. Results indicated that inoculation with different Bradyrhizobia strains improved significantly (p < 0.001 to p < 0.05) height, grain, biomass yield, nodulation, and nitrogen uptake of soybean but less than treatments where phosphorus application was combined to rhizobial inoculation. The most efficient strains identified were FA3 and STM3043 respectively in Northern and Centre Benin. In Northern Benin, the strain FA3 contributed to the increasing of 73% of the grain yield and 62% of the straw yield compared to the control, while in the Centre Benin the strain STM3043 was found to contribute to the increasing of 60% and 66% respectively of the grain and straw yields. Both strains FA3 and STM3043 could be used in cropping systems for improving soybean productivity in Benin.
Keywords: Biofertilizer; cropping systems; nitrogen; yield; Benin